Pendampingan Digitalisasi UMKM Melalui Google Maps Untuk Meningkatkan Visabilitas Usaha, Kecamatan Nongsa, Kota Batam - Anisa Tanasya; Annisya Adelia Pratiwi Aalamsyah; Arimbi Dwi Putri; Dennis Alpian; Liza Saputri; Surya Jaya Diningrat; Wita Afrianti Kurnia Sari; Riesna Apramilda; Muhammad Siddik (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Nongsa District, Batam City, largely still rely on conventional promotion such as word of mouth, despite the district's rapid growth as home to Nongsa Digital Park. This condition limits the market reach of local MSMEs and makes it difficult for them to compete in the digital era. This community service program aims to assist MSMEs in digitalizing their businesses by registering and optimizing their Google Business Profile on Google Maps to improve business visibility. The activity was carried out by the Kuliah Pengabdian Masyarakat (KPM) Team of Group 5, Group 1, Management Study Program, Faculty of Economics and Business, Universitas Ibnu Sina, over a period of 30 days in RT 04 RW 08, Nongsa District, targeting six local MSMEs: Warung Bu Erna Nongsa,Warung Mie AyamBakso Kak Winda, Warung Cik Pen, Warung Sarapan Pagi Meriz, Warung Sembako Nurul, and Warung Tepian Pantai. The method applied was participatory mentoring, comprising initial observation, interviews, hands-on assistance in registering and optimizing Google Maps profiles, independent-use socialization, and final evaluation and documentation. The results show that five MSMEs that had not previously been registered successfully obtained complete Google Maps profiles, while one MSME that had already been registered was successfully optimized through information updates and the addition of new product photos. In addition, the MSME owners gained improved digital literacy in independently managing their businessprofiles. Thisactivityis expected toenhance the visibilityoflocal businesses and serve as a reference for other MSMEs in utilizing Google Maps as a digital promotion medium